Network Economics for Next Generation Networks 6th International Workshop on Internet Charging and QoS Technologies, ICQT 2009, Aachen, Germany, May 11-15, 2009, Proceedings - Reichl, Peter; Stiller, Burkhard; Tuffin, Bruno (Computer Communication Networks and Telecommunications, 2009)
This book constitutes the refereed proceedings of the 6th International Workshop on Internet Charging and QoS Technologies, ICQT 2009, held in Aachen, Germany, in May 2009 collocated with the IFIP Networking 2009 conference. The 9 revised full papers presented together with the extended abstract of a keynote paper were carefully reviewed and selected from a total of 26 submissions. The papers are organized in topical sections on competition models, pricing mechanisms, and economics of inter-domain traffic. Bringing together researchers from the area of technology and economy in both industry and academia to discuss key improvements and to support further progress in these fields, ICQT 2009 features combination of micro-economic models, auctions, game theoretic approaches, peer-to-peer, and IMS-based charging.